(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article investigates color-based phraseological units in Uzbek and English from a comparative linguistic perspective. Phraseological units containing color lexemes reflect cultural values, national mentality, and cognitive perception of the world. Using qualitative and comparative methods, the study analyzes semantic, structural, and pragmatic features of color-related idioms in both languages. The findings show both universal symbolic meanings of colors (such as white for purity and black for negativity) and culture-specific interpretations shaped by historical and social factors. The research contributes to contrastive linguistics, phraseology, and intercultural communication studies.